2018
DOI: 10.1186/s12974-018-1268-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection and immunomodulation following intraspinal axotomy of motoneurons by treatment with adult mesenchymal stem cells

Abstract: BackgroundTreatment of spinal cord injury is dependent on neuronal survival, appropriate synaptic circuit preservation, and inflammatory environment management. In this sense, mesenchymal stem cell (MSC) therapy is a promising tool that can reduce glial reaction and provide trophic factors to lesioned neurons.MethodsLewis adult female rats were submitted to a unilateral ventral funiculus cut at the spinal levels L4, L5, and L6. The animals were divided into the following groups: IA (intramedullary axotomy), IA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 46 publications
1
37
0
4
Order By: Relevance
“…The BPF used in this study is composed of a mixture of a serine protease with thrombin-like enzyme activity, purified from Crotalus durissus terrificus snake venom and buffaloes cryoprecipitate as a source of fibrinogen 53, 30 . Previous studies has shown no cytotoxicity becoming an excellent scaffold for MSC 16, 34, 54, 55 .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The BPF used in this study is composed of a mixture of a serine protease with thrombin-like enzyme activity, purified from Crotalus durissus terrificus snake venom and buffaloes cryoprecipitate as a source of fibrinogen 53, 30 . Previous studies has shown no cytotoxicity becoming an excellent scaffold for MSC 16, 34, 54, 55 .…”
Section: Discussionmentioning
confidence: 86%
“…Spejo et al 55 have demonstrated that MSC therapy is neuroprotective and when associated with a BPF shifts the immune response to a proinflammatory profile. According to them, thet was possible because BPF kept EGFP-MSC at the glial scar region in the ventral funiculus after 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory microenvironment formed following SCI is considered to play an important role in this process. Secondary inflammation, mainly induced by activated macrophages, is one of the most important events in the microenvironment of the injured spinal cord, and this process has recently attracted increasing attention [22,23]. Activated microglia/macrophages have either detrimental or beneficial effects on neural regeneration based on different subsets.…”
Section: Discussionmentioning
confidence: 99%
“…They also can improve axonal regeneration, inhibit demyelination while promoting myelin regeneration [ 16 , 69 72 ], and reconstruct functional neural networks [ 15 ]. It has been proposed that the therapeutic action of implanted MSC in SCI is based on the secretion of a variety of factors, such as NGF, NT-3, and BDNF [ 73 , 74 ]. Furthermore, paracrine immunomodulatory mediators secreted by MSCs can reduce harmful inflammation by inhibiting the differentiation of macrophages and microglia into neurotoxic, proinflammatory M1 subsets and promoting the generation of immunomodulatory M2 subsets which contribute to axonal growth and myelin regeneration [ 75 ].…”
Section: The Effects Of Acupuncture Combined With Mesenchymal Stemmentioning
confidence: 99%